Issues in the Ethics of Using Generative AI - Vogel, Carl (My University, 2024)
Reflections on the relationship between performance enhancing drugs and some forms of academic dishonesty are presented. Generative AI is analyzed as a cognitive infocommunications technology, a technology intended in part to enhance human cognitive capabilities. Research intending to develop and improve generative AI is argued to be ethically sound. The use of generative AI as an enhancement to human cognitive capabilities in direct competitive scenarios such as assessment in education settings and the indirect competition of knowledge production is found to be lacking in ethical merit. The purpose of this article is to stimulate debate by adopting and defending firm, if extreme, positions on the ethical questions at hand.
15th IEEE International Conference on Cognitive Infocommunications
Keywords: Creative Technologies; Digital Engagement; Digital Humanities; Inclusive Society; ARTIFICIAL INTELLIGENCE; Computational Linguistics; Digital Ethics; Large language models; generative AI; Culture; Education; Social exclusion